PEMILIHAN TEKNOLOGI AUDIO YANG TEPAT SEBAGAI MEDIA PEMBELAJARAN UNTUK MAHASISWA UNIVERSITAS TERBUKA - Kurniati, Sri; Sinar, Tengku Eduard Azwar; Aprijani, Dwi Astuti (LPPM Universitas Terbuka, 2009)
The kind of audio technology makes it possible to choose the technology that can make students easy and convenient to access the audio program. Audio streaming technology is technology used to put the audio programs on the website. Available in various formats audio programs that can be used for audio streaming technology. The aim of the research is to make the selection of audio technologies available for use in e-Learning system at the Open University (UT). Data taken with the questionnaire and download audio programs in various formats on the UT website. Data analysis to see the frequency calculations are presented descriptively.The results showed that the 4 (four) format used on audio technology, which is MP3 (MPEG layer 3), WMA (Windows Media Audio), OGG Vorbis, and AAC (Advanced Audio Codec) can be concluded that: most audio format easy to use are MP3, MP3 audio format is the fastest format can be downloaded by students, as well as audio technology that produces the best sound quality is MP3.